A Preliminary Study in Using Computerized Dental Simulators to Train Students at Faculty of Dentistry, King Abdulaziz University - Reem A. Aja; Ghada H. Naguib; Ayman Banjar; Ahmed Abuzinadah (Journal of King Abdulaziz University: Medical Sciences, 2023)
To assess the ability of computerized dental simulators to improve students cavity preparation skills on manikins at Faculty of Dentistry, King Abdulaziz University. Also to determine their capabilities to relate or indicate the level of profession in cavity preparation. Sixty participants formed of students and interns were divided, based on their level of training, into three groups and were assigned randomly to test and control groups. All groups received a baseline assessment of lower second molar class I cavity preparation. The test groups received training on the computerized dental simulators until they reached a target score. The number of attempts and durations were recorded. After completion of training, all groups were assessed again on lower second molar class I cavity preparation by two supervisors based on a detailed rubric given to the students before their baseline and final cavity preparation. The group assignments, level of training, pre- and post- training cavity preparations were masked from the supervisors. There was statistically insignificant improvement in all of the three test groups after computerized dental simulators training, and within the limitations of the study. The computerized dental simulators failed to indicate the level of experience based on reaching the target score.